The Implementation of Good Corporate Governance in the Aerofood ACS Company of Yogyakarta - Garbo, Anom; Wulandari, Dwi Andini (Universitas Islam Indonesia, 2018)
This research focuses on the implementation of Good Corporate Governance concepts in the Aerofood ACS Unit of Yogyakarta. Good Corporate Governance is a procedure for corporate governance that must be carried out and well-structured as a benchmark for the company in running all of its business activities appropriately. The objective of this study is to find out how far the implementation of GCG principles has been applied to ACS Unit of Yogyakarta using indicators that refer to previous research pertaining to the application of GCG in a company in Indonesia. The indicator is taken from the research developed by (Andyoratama & Mustamu, 2013) in the form of an indicator of GCG principles through KNKG (2006). Data collection techniques were carried out by interviewing 3 informants, conducting documentation sessions and the review of literature. The results show that the Aerofood ACS of Yogyakarta company has implemented GCG principles well even though it has not been fully implemented. There are a number of GCG principles that have not been fully addressed, namely the principle of accountability along with CSR implementation indicators from the employees whereas researchers assume that the company is still lacking the maximum welfare to employees, and in terms of the environmental and community sides, the company has not contributed much to its CSR activities. The last obstacle in the company is that the company employees are lack of understanding of GCG. Therefore, the promotion of GCG values needs to be implemented by Aerofood ACS of Yogyakarta.